Attractive lives on attractive pages. Polish illustrated biographical books for young readers - Anita Wincencjusz-Patyna (Problemy Wczesnej Edukacji)
This paper focuses on an exceptionally interesting kind of books dedicated to young readers, quite popular recently in Poland, namely picture biography books for children and teenagers. Polish publishing houses, especially Muchomor from Warsaw, for the last few years have been coming up with a number of intriguing titles, both in the matter of words, and also in their graphic contents, especially the series “Gdansk Trilogy”. Brave ideas, young talents, novel artistic solutions, and original illustrations make the lives of famous people, not so very well-known figures and some unknown names – from both far and near, homeland and neighbourhood history – attractive reading matter. The author also looks back at the history of Polish illustrations included in biographies published in the second half of the 20th century. By combining the traditions of Polish applied graphic art with its up-to-date condition the author wants to trace the impact of the old and the novelty of contemporary books. She wants to stress the expressive power of an image turning illustrations into independent works of art. The number of illustrations and the graphic concept of an up-to-date language of visual forms make them genuine picture stories (especially in the designs by Ignerska). By means of comparative analyses of form and style, as well as a theory of image, she is going to focus on features of the visual side of the aforementioned books. The author would also like to stress the change in the way of perceiving the common history of places with such a complicated history as Gdańsk itself (in which Elisabeth and Johannes Hevelius, Fahrenheit, Schopenhauer, despite their German roots, are treated as part of the common heritage).